2016
DOI: 10.1016/j.janxdis.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Family environment as a moderator of the association between anxiety and suicidal ideation

Abstract: The present study examined associations among anxiety symptoms, anxiety disorder diagnoses, perceptions of family support and conflict, and suicidal ideation (SI) in a clinical sample of psychiatrically hospitalized adolescents. Participants were 185 adolescents (72% female; 84% white, mean age = 15.02 years, SD = 1.33) hospitalized on an acute psychiatric inpatient unit. Results indicated that anxiety disorders and symptoms were positively associated with SI, even after controlling for mood disorder diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 37 publications
0
13
1
2
Order By: Relevance
“…Li (2015) found that older adults with good support from children and neighbors were less likely to have SI. Machell et al (2016) found that adolescent perceptions of family conflict demonstrated an independent association with SI. In agreement with these studies, the current study also indicated the important role of family support in SI.…”
Section: Discussionmentioning
confidence: 93%
“…Li (2015) found that older adults with good support from children and neighbors were less likely to have SI. Machell et al (2016) found that adolescent perceptions of family conflict demonstrated an independent association with SI. In agreement with these studies, the current study also indicated the important role of family support in SI.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, individuals with higher levels of resilience were less likely to suffer from anxiety and depression by linking the results that they evaluate the same thing more positively, and less psychological resources were needed to cope with life-threatening events. The review of Schiele and Domschke (2018) showed that resilient function was associated with positive cognitive emotion regulation strategies, which could decrease the risk of suffering from mental disorders such as depression or anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a chaotic household seems to increase the suicide risk among young people, and previous findings have identified family support as an important intervention target to decrease suicide risk among anxious young people. 55 Family support and involvement in intervention for those at risk is another potentially successful pathway. 56 Lastly, the fact that indicators of childhood adversity often co-occur might have important implications for intervention.…”
Section: <15mentioning
confidence: 99%